Opportunities, constraints and constrained opportunities – A study on mothers’ working time patterns in 22 European countries - Salin, Milla (fi=Väestöliitto|en=The Population Research Institute|, 2014)
The aim of this study was to analyse mothers’ working time patterns across 22 European countries. The focus was on three questions: how much mothers prefer to work, how much they actually work, and to what degree their preferred and actual working times are (in)consistent with each other. The focus was on cross-national differences in mothers’ working time patterns, comparison of mothers’ working times to that of childless women and fathers, as well as on individual- and country-level factors that explain the variation between them. In the theoretical background, the departure point was an integrative theoretical approach where the assumption is that there are various kinds of explanations for the differences in mothers’ working time patterns – namely structural, cultural and institutional – , and that these factors are laid in two levels: individual- and country-levels. Data were extracted from the European Social Survey (ESS) 2010 / 2011. The results showed that mothers’ working time patterns, both preferred and actual working times, varied across European countries. Four clusters were formed to illustrate the differences. In the full-time pattern, full-time work was the most important form of work, leaving all other working time forms marginal. The full-time pattern was perceived in terms of preferred working times in Bulgaria and Portugal. In polarised pattern countries, fulltime work was also important, but it was accompanied by a large share of mothers not working at all. In the case of preferred working times, many Eastern and Southern European countries followed it whereas in terms of actual working times it included all Eastern and Southern European countries as well as Finland. The combination pattern was characterised by the importance of long part-time hours and full-time work. It was the preferred working time pattern in the Nordic countries, France, Slovenia, and Spain, but Belgium, Denmark, France, Norway, and Sweden followed it in terms of actual working times. The fourth cluster that described mothers’ working times was called the part-time pattern, and it was illustrated by the prevalence of short and long part-time work. In the case of preferred working times, it was followed in Belgium, Germany, Ireland, the Netherlands and Switzerland. Besides Belgium, the part-time pattern was followed in the same countries in terms of actual working times. The consistency between preferred and actual working times was rather strong in a majority of countries. However, six countries fell under different working time patterns when preferred and actual working times were compared. Comparison of working mothers’, childless women’s, and fathers’ working times showed that differences between these groups were surprisingly small. It was only in part-time pattern countries that working mothers worked significantly shorter hours than working childless women and fathers. Results therefore revealed that when mothers’ working times are under study, an important question regarding the population examined is whether it consists of all mothers or only working mothers. Results moreover supported the use of the integrative theoretical approach when studying mothers’ working time patterns. Results indicate that mothers’ working time patterns in all countries are shaped by various opportunities and constraints, which are comprised of structural, cultural, institutional, and individual-level factors.

Mahdollisuuksia, rajoitteita ja rajoitettuja mahdollisuuksia – Tutkimus äitien työaikamalleista 22 Euroopan maassa. Tutkimuksessa tarkasteltiin äitien työaikamalleja 22 Euroopan maassa. Äitien työaikaa lähestyttiin kolmesta näkökulmasta: kuinka paljon äidit haluavat tehdä töitä, kuinka paljon äidit todellisuudessa tekevät töitä sekä mikä on työaikatoiveiden ja todellisen työajan välinen suhde. Kiinnostuksen kohteena olivat työajoissa havaittavat maiden väliset erot, äitien työaikojen erot lapsettomiin naisiin ja isiin sekä äitien työaikojen eroja selittävät yksilö- ja maatason tekijät. Tutkimuksen teoreettisessa viitekehyksessä hyödynnettiin integroivaa teoreettista lähestymistapaa. Integroivan teoreettisen lähestymistavan mukaan selityksiä äitien työssäkäyntimallien eroihin on etsittävä niin rakenteellisista, kulttuurisista kuin institutionaalisistakin tekijöistä. Näitä tekijöitä löytyy kahdelta tasolta: yksilö- ja maatasolta. Aineistona tutkimuksessa käytettiin kvantitatiivista European Social Survey (ESS) -aineistoa vuosilta 2010 / 2011. Tutkimustulokset osoittivat, että äitien työaikamallit vaihtelivat eri Euroopan maissa toivotun ja todellisen työajan suhteen. Havaittujen erojen pohjalta muodostettiin neljä työaikamallia, jotka kuvastivat eri työaikojen merkitystä äitien työssäkäynnissä. Kokoaikatyön mallissa kokoaikatyö oli vallitsevassa asemassa muiden työaikamuotojen jäädessä marginaalisiksi. Tämä malli kuvasti toivottuja työaikoja Bulgariassa ja Portugalissa. Polarisoituneessa mallissa työssäkäymättömyys ja kokoaikatyö olivat tärkeimmät työaikamuodot. Toivottujen työaikojen osalta malliin kuuluivat monet Etelä ja Itä-Euroopan maat, todellisen työajan osalta kaikki Etelä- ja Itä-Euroopan maat sekä Suomi. Kombinaatiomallia kuvasti sekä pitkän osa-aikatyön että kokoaikatyön tärkeys. Se oli toivottu työaikamalli Pohjoismaissa, Espanjassa, Ranskassa ja Sloveniassa. Sen sijaan todellisen työajan osalta kombinaatiomalli löytyi Belgiasta, Norjasta, Ranskasta, Ruotsista ja Tanskasta. Neljäs äitien työaikoja kuvaava malli oli osa-aikamalli, jossa lyhyt ja pitkä osa-aikatyö olivat yleisimpiä. Tämä oli toivottu työaikamalli Alankomaissa, Belgiassa, Irlannissa, Isossa-Britanniassa, Saksassa ja Sveitsissä. Belgiaa lukuun ottamatta samat maat kuuluivat osa-aikamalliin myös todellisen työajan suhteen. Äitien työaikatoiveiden ja todellisen työajan välinen suhde oli siten monessa maassa melko vahva. Kuitenkin kuudessa maassa vaihdettiin työaikamallista toiseen tutkittaessa toivottua ja todellista työaikaa. Työssäkäyvien äitien työaikojen erot työssäkäyviin lapsettomiin naisiin ja isiin olivat monissa maissa yllättävän pienet. Vain osa-aikatyömallin maissa työssäkäyvien äitien työajat olivat selkeästi lyhyemmät kuin työssäkäyvien lapsettomien naisten tai isien työajat. Tulokset osoittivatkin, että äitien työaikoja tutkittaessa on tärkeää huomioida, tutkitaanko vain työssäkäyviä äitejä vai otetaanko tarkasteluun mukaan myös työssäkäymättömät äidit. Tulokset tukivat integroivan teoreettisen lähestymistavan merkitystä äitien työaikojen erojen selittämisessä. Äitien työaikamalleja muovasivat kaikissa tässä tutkimuksessa tarkastelluissa maissa erilaiset mahdollisuudet ja rajoitteet, joita ovat niin rakenteelliset, kulttuuriset, institutionaaliset kuin yksilöllisetkin tekijät.